KORELASI KEPEMIMPINAN DENGAN DINAMIKA KELOMPOK BUDIDAYA IKAN PENINGKATAN PROMOSI KESEHATAN GIZI MASYARAKAT - Nuraini, Novia -; Batlajery, Jomima; Fratidhina, Yudhia; Hamidah, Hamidah; Yantina, Debbi (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
The fisheries sector has the potential to be an important part of world food security. This can be seen from the large number of fish commodity exports from developing countries in 2014 amounting to 50% of total exports. The aim of this research is to determine the assessment of the leadership of the group leader and the dynamics of the catfish cultivation group and to determine the relationship between the leadership of the group leader and the dynamics of the catfish cultivation group in Tualang Village. The research used is descriptive in nature. Respondents in this study totaled 17 people. The analysis used to analyze the leadership assessment of the group leader and group dynamics uses Likert scale analysis. Meanwhile, to analyze the relationship between group leader leadership and group dynamics using Spearman rank test analysis. The research results showed that the level of leadership of the head of the catfish cultivator group was 594 in the "Very good" category and the level of dynamism of the catfish cultivator group was 2,205 in the "Dynamic" category. Meanwhile, based on the Spearman rank test on the relationship between the leadership of the group leader and the group dynamics of catfish cultivators, it shows a correlation coefficient value of 0.658, which means there is a strong relationship between the leadership of the group leader and group dynamics.